Myth and Popular Heritage in Walid Seif Poetry - Diana Majed Huseen Nada (My University, 2013)
This research discusses the myth and folklore in the poetry of Walid Seif sheding light on the legendary and folkloric symbols employed by waleed Seif in his three Divans: Poems in the Conquest Era, Tattoo on the Arm of Khadra, and Epic of the Palestinians as well as his two poems: The Search for Abdallah Albarii and Relove. Concerning the folklore, I made brief description on: folkloric proverb, tale, song; customs and habits, costumes as well as folkloric words. Then I studied their employment in Waleed Seif’s poetry where I extracted the poetic samples that contained these symbols then I analyzed and connected them with the original folkloric texts and showed the intentions of Waleed Seif’s employment of these symbols. I did the same with the folkloric symbols clarifying the reason behind using them by Waleed Seif. Some of these symbols include: The Symbols of Ishtar, The Legendary of the Phoenix, Azurees, and the Bride of the Sea. I, then, moved to the artistic aspect where I tracked the consequences of employing the folklore and the myth on the structure of the Waleed’s poems focusing on language, rhythm, dramatic structure, art image, repetition, and ellipsis. Finally, my research came to the following conclusions: The inspiration of the folklore and the myth in Waleed’s writings is neither haphazard or superficial; on the contrary, it reflects a high level of knowledge in various fields. As such, each word written by Waleed has its effects and in many cases, it carries many meanings. His usage for the folklore is not a mere habit or a decoration for his poems. However, this employment is used insightfully. Moreover, Waleed Seif’s poetry represents a Palestinian folkloric document which exhibits a lot of folkloric traditions and customs rarely found in our modern times and may have been perished.

تناولتُ في هذا البحث المعنون بـ(الأسطورة والموروث الشعبي في شعر وليد سيف)، الرموز التراثية والأسطورية التي وظفها سيف في دواوينه الثلاثة: (قصائد في زمن الفتح 1969) و(وشم على ذراع خضرة1971) و(تغريبة بني فلسطين 1980)، وقصيدتي (البحث عن عبد الله البري) و(الحب ثانية). وفي ما يخصّ الموروث الشعبي، فقد قدمت حديثا مختصرا عن: المثل الشعبي، والحكاية الشعبية، والأغنية الشعبية، والعادات والتقاليد، والأزياء والألفاظ الشعبية، ثمّ عالجت توظيفها في شعر سيف، إذ حصرت النّماذج الشعرية التي احتوت تلك الرموز، وحلّلتها، وربطّتها بالنصوص الشعبية الأصلية، ووضّحت مقصد وليد سيف من توظيفها. وفعلت الشيء نفسه مع الرموز الأسطورية، التي تناولتها بالتحليل، والدراسة، ووضّحت سبب لجوء وليد سيف إليها،ومنها:رموز عشتار، وأسطورة الفينيق، وأزوريس، وعروس البحر. ثم انتقلت إلى الجانب الفنّي، وفيه رصدّت تأثير استخدام الموروث الشعبي، والأسطوري على بنية القصيدة عند سيف، من حيث اللغة، والموسيقى، والبناء الدرامي، والصورة الفنية، والتكرار، والحذف. وأخيرا رصدتُ أهمّ النتائج التي توصلت إليها من خلال دراستي، وأهمها: أن استلهام وليد سيف للموروث الشعبي والأسطوري لم يكن عبثيا، ولم يكن سطحيا، وكان هدفه الأساسي من هذا التوظيف تعرية الواقع السياسي،واستثارة الزعامات العربية لتفيق من سباتها. ولم يكن توظيفه للتراث بنوعيه مجرّد عادة اتُّبعت عند الشعراء المعاصرين، أو مجرد زينة يزيّن بها قصائده، بل وُظّفت بكلّ عمق ودراية، إضافة إلى أنّ شعره مثّل وثيقة شعبية فلسطينية، فقد رصدتُُ من خلاله كثيرا من العادات والتقاليد الشعبية التي قلّتْ كثيرا في عصرنا وربّما اندثرت
الاسطورة والمروث الشعبي في شعر وليد سيف